Pola Saluran Pemasaran Ikan Di Daerah Istimewa Yogyakarta (DIY) - Cahya Purnomo (Sekolah Tinggi Maritim Yogyakarta, 2018)
This study aims to analyse fish's marketing channel pattern of Yogyakarta Region. Data gathering by purposive sampling, that comprise 2 fish auctions of Gunung Kidul District and 1 of Kulon Progo District, 6 fishermans of Gunung Kidul District and 4 from Kulon Progo District, 4 intermediary trader of Gunung Kidul District and 3 from Kulon Progo District. Analysis used by describe fish's marketing channel pattern and counts to fisherman's share. The result showed that 60% of fish circulating in DIY come from the North Coast of Java and 40% from Yogyakarta Region. Yogyakarta Region fish production is exported 40%, especially high-value fish. There are 4 patterns of marketing channels. Pattern 1 is fisherman - fish auctions – end consumer by fisherman's share 95 % for all species, this type is most effective channel. Pattern 2 is is fisherman – fish auctions – collector traders – retailer trader – end consumer by variety fisherman's share from 48 % so 71 %. Pattern 3 is is fisherman – fish auctions – collector traders – restaurant – end consumer by variety fisherman's share from 39 % sampai 64 %. Pattern 4 is fisherman – fish auctions – processing industry – end consumer, that fisherman's share is known to collector traders only from 61 % to 85 %. All fish transaction always through fish auctions as mediator between fisherman and next marketing stakeholder.